Antidiabetic Activities of Malaysian Agarwood (Aquilaria SPP) Leaves Extract - Nur Liyana, Zulkifle; Nor Adila, Mhd Omar; Saiful Nizam, Tajuddin; Mohd Rosly, Shaari (2013)
Aquilaria SPP or agarwood were reported to have pharmacological activities. There was a report of one diabetic patient who was drank infusion of agarwood leaf was found to have blood sugar return to normal.